Corporate Governance Development In Sri Lanka: Prospects And Problems - Senaratne, S.; Gunaratne, P. S. M. (My University, 2008)
The study appraises the current state of corporate governance development in Sri Lanka in relation to the publicly traded (listed) companies to identify the prospects and the associated problems in the socio-economic context of the country. The study finds that corporate governance best practices have evolved in Sri Lanka over a period of time from a voluntary code of compliance to the present mandatory rules. Accordingly, the study derives the existing corporate governance model for Sri Lankan listed companies, which is a mixture of both mandatory and voluntary rules on corporate governance and it has been developed in line with the Anglo-Saxon model of corporate governance due to both historical and economic reasons. Although the Anglo-Saxon model has instilled some good corporate governance practices in these companies, the institutional conditions necessary for its successful application are lacking in Sri Lanka mainly owing to the concentrated corporate ownership structure in the country. This raises serious concerns as to the implementation of an independent director system and the protection of minority shareholder rights in Sri Lanka. However, the ownership concentration is a distinguishing feature of the insiderbased corporate governance model of Continental European and Asian countries. Thus, a hybrid system of corporate governance is practised presently in Sri Lanka, which in turn indicates that the traditional dichotomy of insider and outsider models of corporate governance is not suitable in the Sri Lankan context. Hence, the best model of corporate governance for Sri Lanka is one that could address effectively the critical corporate governance issues of the country.